The long and winding road to Arab democracy - Erik Boel (Danish Institute for International Studies (DIIS), 2005)
From Marrakesh to Cairo and from Ramallah to Riyadh, the Arabs debate and reflect on their own society as never done before. However, the road to democratisation in that region is long and winding. This paper analyses the experience the Americans have acquired regarding that goal which the US has placed on top of the international agenda. Experience, which can also be useful in a Danish context. – – – Fra Marrakesh til Cairo og fra Ramallah til Riyadh debatterer og reflekterer araberne i øjeblikket over deres egne samfunds fremtid som aldrig før. Imidlertid er vejen til en demokratisering af denne region lang og snoet. Dette paper analyserer de amerikanske erfaringer for at nå dette mål, som USA har placeret øverst på den internationale dagsorden. Erfaringer som også kan være nyttige i en dansk sammenhæng.
Keywords: 330